2019
DOI: 10.22460/project.v2i3.p325-331
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grammar Skill Using Egra Technique for the Students’ Eighth Grade at SMPN 5 Cimahi

Abstract: Grammar is one part to improve four skills that we also known. To enhance grammar skill we have to prefer the accurately method as a way in studying grammar. The researcher was chosen Exposure, Generalization, Reinforcement, and Application (EGRA) technique as a method to teaching English grammar to students’ eigtht grade at SMPN 5 Cimahi. It was arranged with using pre-experimental method, peculiarly one-group pre-test post-test design. The technique showed that can develop grammar skill students’. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The effectiveness of the EGRA method is reinforced by Kusumastuti et al, (2019) and Pilu et al, (2020). Kusumastuti et al, (2019) in their research improving grammar skills with EGRA method for junior high school. The research found that the EGRA method is effective and significant for teaching passive voice.…”
Section: Egramentioning
confidence: 92%
“…The effectiveness of the EGRA method is reinforced by Kusumastuti et al, (2019) and Pilu et al, (2020). Kusumastuti et al, (2019) in their research improving grammar skills with EGRA method for junior high school. The research found that the EGRA method is effective and significant for teaching passive voice.…”
Section: Egramentioning
confidence: 92%